2020
DOI: 10.1155/2020/4548012
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-Gamma Agonist Pioglitazone Reduced CD68+ but Not CD163+ Macrophage Dermal Infiltration in Obese Psoriatic Patients

Abstract: Background. Macrophages are of great importance in the development of obesity and psoriasis. Signaling via PPAR-γ in certain macrophage populations is associated with M2-like features and anti-inflammatory profile. In this research, we evaluated the anti-inflammatory action of pioglitazone by the immunohistochemical study of M1 and M2 macrophages in psoriasis-affected skin in obese patients. Methods. We used immunohistochemistry to characterize CD68+ and CD163+ macrophages and pathomorphological description of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
(66 reference statements)
0
9
0
2
Order By: Relevance
“…The synthetic ligands mainly include thiazolidinediones (troglitazone, rosiglitazone, and pioglitazone), nonsteroidal anti-inflammatory drugs, and leukotriene D4 receptor antagonists. 19 The N-terminal domain of PPAR-γ contains a protein kinase phosphorylation site that can be activated by mitogens. PPAR-γ, after being activated by ligands, forms a heterodimer with the retinoic acid receptor (RXR), which then binds with the peroxisome proliferator response element (PPRE) of the target gene promoter to activate target gene transcription of factors that have a variety of biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic ligands mainly include thiazolidinediones (troglitazone, rosiglitazone, and pioglitazone), nonsteroidal anti-inflammatory drugs, and leukotriene D4 receptor antagonists. 19 The N-terminal domain of PPAR-γ contains a protein kinase phosphorylation site that can be activated by mitogens. PPAR-γ, after being activated by ligands, forms a heterodimer with the retinoic acid receptor (RXR), which then binds with the peroxisome proliferator response element (PPRE) of the target gene promoter to activate target gene transcription of factors that have a variety of biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…A case-controlled study among 45 Egyptian psoriatic patients showed the statistically significant association of the Ala allele of the PPAR-γ gene (Pro12Ala polymorphism) with obesity and psoriasis occurrence, although no correlation with MS incidence was found [77]. Additionally, a pilot study carried out in the obese psoriatic patients demonstrated the anti-inflammatory skin effect of the orally administered PPAR-γ agonist (pioglitazone), which was confirmed by the immunohistochemical detection [78].…”
Section: Genetic Pathways Of Obesity Abnormal Body Mass Index (Bmi) and Psoriasismentioning
confidence: 94%
“…These cell interaction networks and specific molecules suggest optimizational targets for PLC immunotherapy. Hepatic macrophages play crucial roles in hepatocarcinogenesis, both the positive and negative side with signal induced differential phenotypes to our knowledge, such as negatively releasing tumor promoting cytokines in pre-metastatic niche formation and extravasation, positively eliminating hepatoma cells by phagocytosis in cancer cell arrival stage [ 127 130 ]. CD169 + macrophage subpopulations were found to enhance the cytotoxicity and amplification capability of CD8 + T cells against HCC under anti-CD3 irritation, and exerted suppressive effects on tumor progression [ 131 ].…”
Section: Active Cellular Immunotherapy In Primary Liver Cancermentioning
confidence: 99%